Corrosion and Deposition of HVDC Converter Valve. Issue 6 (March 2020) - Cui, Pengfei; Guan, Shengli; Guo, Jianbao; Wang, Guangwu; Wang, Haijun; Chen, Jianye; Huang, Kefeng; Geng, Man; Yang, Weilong; Deng, Longlong
Abstract: The corrosion of the light-triggered converter radiator and the fouling of the voltage-equalizing electrode are always the technical problems to be solved in the field of HVDC, which seriously affects the stable operation of the DC system. In this paper, the material properties, manufacturing process and actual running process of radiators are studied deeply through the analysis of composition and morphology. Main reason for the corrosion of radiator is the turbulent corrosion caused by the cold water flushing in the converter valve, and the electrochemical corrosion is only a small part of the corrosion of radiator. At the same time, in order to verify the scaling process of the voltage-equalizing electrode, a test platform was built, and the experiment was carried out by using aluminium ion input acceleration method. The experimental results show that the aluminum ions precipitated by the corrosion of radiators are transferred directionally to the high-potential electrode under the action of electric field to form aluminium hydroxide precipitation. The precipitation of aluminium hydroxide leads to the scaling of the equalizing electrode, which is getting worse every year.